Guidelines for stocking community fish refuge systems - Ou, Phichong; Sean, Vichet; Sun, Vathanak; Chhy, Savry; Lim, Nget; Mam, Sovannary; Phin, Phearum; Eng, Kimleng; Samon, Channa; Gregory, Rick (WorldFish, 2024)
The stocking of CFR ponds is an important action that can help enhance fish stocks, conserve endangered species, and ensure the sustainable use of natural resources. The Fisheries Administration, in collaboration with WorldFish and the GIZ-SAFR project, produced this guide on stocking of CFR ponds as a contribution to meeting this purpose. This guide outlines the importance of fish stocking, steps in the stocking process, the species and sources of stocking materials, and actions to be taken before and after stocking. We hope that this guide meets the needs of the CFR Management Committees to implement interventions in their areas and serve to inform policy making and planning on protecting and managing rice field fisheries in a balanced way, now and for the future.